PENERAPAN METODE GAMES DALAM PENGAJARAN BAHASA INGGRIS HUKUM - Windiahsari, - (Lembaran Ilmu Kependidikan, 2009)
Learning a new language can be a very hard task. However, the result is beingable to communicate with people in different language and culture from around theworld. The learning process of a new language takes time and challenge. It should bedone continuously in such a long time. In the past, English was taught in a traditionalway and made the learners bored of studying it. It is necessary to find out an interactiveand interesting way of teaching English. One of them is using games in the process ofteaching and learning English. The English language of Law is a new lesson in theLaw Faculty in UNNES. It needs a new paradigm of teaching it since it belongs toEnglish for Specific Purposes. It is different from general English in that the languagehas special lexical and linguistic features. The language of law is divided into two,spoken and written. The spoken form is used in the pedagogical, academic andprofessional fields. The use of spoken language of law in pedagogical field is forlecturing and moot. In the academic field, it is used for interacting among colleaguessuch as having seminars or discussion. In the professional field, it is used for lawyerclientconsultation and counsel-witness examination. The written form of language oflaw is used in four areas; pedagogic, academic, juridic, and legislative. The example ofwritten form used in the pedagogic is the law textbook; in the academic is articles oflaw journal; in the juridic is the legal judgment and the legal cases; in the legislativecan be seen in contracts, agreements, insurance policies, legislation rules andregulations. To transform the new register of English language of law with aninteresting and interactive way, games can be one of the solutions.Kata kunci: games, bahasa Inggris, dan hukum